Hemodynamic characterization of recombinant inbred strains: twenty years later - Kunes, Jaroslav; Dobesová, Zdenka; Musilová, Alena; Zídek, Václav; Vorlícek, Jaroslav; Pravenec, Michal; Kren, Vladimír; Zicha, Josef (Hypertension research, 2008)
Recombinant inbred (RI) strains (Prague HXB/BXH set) represent a unique model that allows for permanent summation of genetic and physiological information as well as the study of age-dependent changes in phenotypes and/or gene regulation. This study compared blood pressure (BP) measured in adult animals of RI strains by radiotelemetry with BP values obtained in conscious rats of comparable age subjected to short-term carotid catheterization or with those obtained by direct carotid puncture under ether anesthesia (almost 20 years ago). After radiotelemetry recording, the contribution of major vasoactive systems to BP maintenance was studied by consecutive inhibition of the renin-angiotensin system (RAS), sympathetic nervous system (SNS), and nitric oxide synthase. We found highly significant interrelationships among baseline BP values obtained by radiotelemetry, carotid catheterization, or carotid puncture. This indicates considerable stability of RI strains over the course of their long existence, and confirms the reliability of BP values used for genetic studies performed in the past. Subsequent analysis of vasoactive system participation revealed the importance of SNS for the maintenance of BP, as determined by either radiotelemetry or catheterization. The BP of catheterized rats also correlated closely with acute captopril-induced BP changes, but this was not the case for rats measured by radiotelemetry. NO-dependent vasodilatation matched the BP effects of SNS and RAS in both measuring conditions. Residual BP (recorded at sodium nitroprusside-induced dilatation of resistance vessels) was also responsible for a significant portion of the BP variation in RI strains. Our study confirms the validity of RI strains for the further genetic and physiological research of hypertension.
Keywords: inbrední kmeny potkanů; Rats, Inbred Strains; Nitric Oxide Synthase; Rats; krevní tlak; Telemetry; Hypertension; rekombinantní proteiny; Disease Models, Animal; potkani inbrední SHR; renin-angiotensin systém; Monitoring, Physiologic; Heart Rate; krysa rodu Rattus; Catheterization; srdeční frekvence; antihypertenziva; Organ Size; velikost orgánu; Antihypertensive Agents; modely nemocí na zvířatech; synthasa oxidu dusnatého; zvířata; Blood Pressure; telemetrie; Renin-Angiotensin System; hypertenze; sympatický nervový systém; Sympathetic Nervous System; monitorování fyziologických funkcí; Rats, Inbred SHR; katetrizace; Recombinant Proteins; Animals